Failure of auditors: The lack of compliance for business combinations in China. Issue 3 (7th January 2013) - Taplin, Ross; Zhao, Yafang; Brown, Alistair
Abstract This empirical study investigates the compliance of 344 Chinese listed companies with the Accounting Standard for Enterprises No. 20‐Business Combination, a mandatory reporting standard applicable to companies involved in business combinations. China has recently reformed its auditing sector, enabling private firms to provide auditing services. The results of the study show a low level of compliance by Chinese listed companies. While companies audited by Chinese domestic auditors have significantly lower compliance than companies audited by Big Four auditors on supplementary disclosure that is mandatory under the Chinese accounting standards, compliance remains low even after companies receive unqualified reports from these international auditors. There appears to be a lack of commitment, and possibly expertise, among Big Four auditors, in fully applying the reporting requirements of the business combination standard in a Chinese setting. This raises concerns about the independence of Chinese auditing in disclosing reliable information about business combinations. Broader theoretical contributions of the paper go beyond the Chinese context by problematizing whether well‐resourced international auditors uphold internationally expected standards or succumb to local non‐compliant practices.